The Pre-operative Embolization of Meningioma Leads to Reduced Operating Time and Less Intraoperative Bleeding - Khan, Awais Ali; Khan, Habib Ullah; Bangash, Khurshid Ali; Qasmi, Shahzad Ahmed; Ahmed, Syed Adeel; Hashmat, Asif; Shamim, Babar (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine the efficacy of pre-operative meningioma embolization in terms of operating time and intraoperative bleeding.Study Design: Prospective longitudinal study.Place and Duration of Study: Department of Neurosurgery, Combined Military Hospital, Rawalpindi Pakistan, from Jan to Dec 2020.Methodology: Twelve diagnosed cases of intracerebral meningioma were included in the study. The patients were diagnosed cases of meningioma as per pre-operative signs and symptoms, radiological confirmation was done with magnetic resonance imaging, and all were subjected to pre-operative embolization of the tumour with catheter advancement in the arterial system and embolizing the target vessels with polyvinyl alcohol particles, followed by craniotomy and excision of the tumour.Results: The mean age of the patients was 47±672. 24 years. The mean operating time (from the incision to closure) was 96.17±10.23 minutes. In contrast, the intraoperative blood loss was 325.33±15.43 ml. Six (50.00%) individuals had parasagittal meningioma, 4(33.33%) were of cerebral convexity, while 2(16.66%) had lesions at sphenoid wing.Conclusion: Meningioma is a quite vascular tumour, and the operative outcome can be improved by pre-operative angioembolization. The reduced vascularity makes the resection easier by decreasing the per-op bleed and operating time.Keywords: Intraoperative bleed, Meningioma, Operating time, Pre-operative embolization.